Supported Ruthenium Phosphide as a Promising Catalyst for Selective Hydrogenation of Sugars - Popp, Lukas; Kampe, Philipp; Fritsch, Birk; Hutzler, Andreas; Poller, Maximilian J.; Albert, Jakob; Schühle, Patrick (European Journal of Inorganic Chemistry, 2024)
This work demonstrates that supported ruthenium phosphides (RuP2) are attractive catalysts for selective production of alditols by sugar hydrogenation. In our studies, carbon supported RuP2 with a ruthenium content of 5 wt.– % led to the highest activity in xylose hydrogenation and to nearly 100 % yield for xylitol. ICP-OES and XRD measurements revealed the stability of this novel RuP2/C catalyst under typical hydrogenation conditions (50 barH2, 120 °C) in aqueous phase. Furthermore, STEM-EDX illustrated the close proximity of ruthenium and phosphorous on the catalyst site and the formation of nanoparticles in the size of 2–4 nm. The catalyst system was successfully applied for the selective hydrogenation of further sugar substrates, including glucose, fructose, and disaccharides, such as cellobiose and sucrose. Here, the RuP2/C revealed its bifunctional acidic/metallic character, enabling in a tandem reaction the hydrolysis of disaccharides, directly followed by a selective hydrogenation to form sugar alcohols in high yield.
CRIS-Team Scopus Importer:2024-06-21
Keywords: ruthenium phosphide; selective hydrogenation; sugar alcohols; sugar hydrogenation; Transition metal phosphides